A Quantitative Approach for the Determination of Elemental Impurities in Zinc Orotate Dihydrate Drug Substance by ICP-MS Method (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
These days elemental impurities are commonly present in active pharmaceutical ingredients, raw materials, during synthesis of compounds, drug excipients, finished products, equipment, container and closures. ICPMS is one of the advanced techniques to analyse elemental impurities in drug substances. An ICP-MS method was developed and validated for testing 17 elements, namely, V, Co, Ni, As, Se, Ru, Rh, Pd, Ag, Cd, Os, Ir, Pt, Au, Hg, Tl and Pb in zinc orotate dihydrate. The samples were analysed after diluting with concentrated nitric acid and concentrated hydrochloric acid. Li, Y, Tl, Co & Ce were assigned tuning solution to correct the baseline drift and matrix interference. The RF power was 1550 W, RF matching was 1.80 V, sample depth was 8.0 mm, nebulizer gas flow was 1.01 L/min, nebulizer pump flow was 0.10 rps, spray chamber temperature 2o C, He flow rate was 4.3 ml/min and the energy discrimination rate was 3.0 V. All 17 elements exhibited excellent linearity in their testing range, with a coefficient of determination ≥ 0.9996. The limits of detection of the 17 elements were within the range of 0.0004–0.00411ppm. The intra- and inter-day precision (relative standard deviation) was < 6.4%. The recoveries of the spiked standard for all elements were 88.5–108.2%. Among the17 elements of the zinc orotate dihydrate, the measured results of all the 17 elements were within the specified range, and the results of the all the elements were also satisfactory. The developed method was simple, rapid, and effective. This method can be a powerful tool and imperative technology for the quantification of compounds in drug substances and pharmaceutical industries.